Impact of Macroeconomic Variables on Stock Market Capitalization in Nepal - Ghimire, Ashish; Miya, Rahim; Guragain, Sadhana; Upreti, Sajita; Poudel, Shankar; Okheda, Shyam Bahadur (Economic Review of Nepal, 2025)
The current research focuses on how some major macroeconomic factors affect the stock market capitalization in Nepal based on the annual observed data between 2000 and 2023. Using the Autoregressive Distributed Lag (ARDL) model, short-run and long-run relationships show the total stock market value performance in relation to six macroeconomic indicators which are the GDP, inflation, money supply, the private sector credit, remittance inflows, and the interest rate. The findings indicate that private sector credit and remittance significantly and positively influence the stock market capitalization in the long-run, indicating that financial deepening and external financial flows are conducive to the growth of Nepal capital market. Interest rate was discovered to be affected negatively in the short run whereas surprisingly the GDP had negative relation in the long run which means there is poor connection between the stock market and real economic growth. Inflation and money supply were statistically not supportive for stock market capitalization in Nepal. Those results put emphasis on the need to enhance the structural relationship between financial markets and essentials in the economy in Nepal.